Glucose regulation in the methylotrophic yeast Hansenula (Ogataea) polymorpha is mediated by a putative transceptor Gcr1. (October 2018) - Stasyk, Olena G.; Denega, Iryna O.; Padhorny, Dzmitry; Dmytruk, Kostyantyn V.; Kozakov, Dima; Abbas, Charles; Stasyk, Oleh V.
Abstract: The Hp Gcr1, a hexose transporter homologue from the methylotrophic yeast Hansenula ( Ogataea ) polymorpha, was previously identified as being involved in glucose repression. Intriguingly, potential Hp Gcr1 orthologues are found only in the genomes of a few yeasts phylogenetically closely related to H. polymorpha, but are absent in all other yeasts. The other closest Hp Gcr1 homologues are fungal high-affinity glucose symporters or putative transceptors suggesting a possible Hp Gcr1 origin due to a specific archaic gene retention or via horizontal gene transfer from Eurotiales fungi. Herein we report that, similarly to other yeast non-transporting glucose sensors, the substitution of the conserved arginine residue converts Hp Gcr1 R165K into a constitutively signaling form. Synthesis of Hp Gcr1 R165K in gcr1 Δ did not restore glucose transport or repression but instead profoundly impaired growth independent of carbon source used. Simultaneously, gcr1 Δ was impaired in transcriptional induction of repressible peroxisomal alcohol oxidase and in growth on methanol. Overexpression of the functional transporter Hp Hxt1 in gcr1 Δ partially restored growth on glucose and glucose repression but did not rescue impaired growth on methanol. Heterologous expression of Hp Gcr1 in a Saccharomyces cerevisiae hxt- null strain did not restore glucose uptake due to protein mislocalization. However, Hp Gcr1 overexpression in H. polymorpha led to increased sensitivity to extracellular 2-deoxyglucose, suggesting Hp Gcr1 is a functional glucose carrier. The combined data suggest that Hp Gcr1 represents a novel type of yeast glucose transceptor functioning also in the absence of glucose.